2010
DOI: 10.1111/j.1399-0039.2010.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of natural killer cells with high cytotoxicity by K562 cells modified to co-express major histocompatibility complex class I chain-related protein A, 4-1BB ligand, and interleukin-15

Abstract: A large number of natural killer (NK) cells with high function are expected to generate especially in tumor adoptive immunotherapy. Here K562 cells were genetically modified to co-express major histocompatibility complex class I chain-related protein A (MICA), 4-1BB ligand, and IL-15, called K562-MICA-4-1BBL-IL-15. The modified K562 cells not only promoted activation, proliferation, and survival of NK cells, but also enhanced NK cell cytotoxicity. In long-term culture tests, K562-MICA-4-1BBL-IL-15 cells stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 26 publications
(32 reference statements)
0
49
0
Order By: Relevance
“…Addition of irradiated B cells led to approximately 740-fold increase in NK cell number; these results are comparable with the genetically modified approaches described earlier. A recent report describes the use of K562 cells expressing membranebound IL-21 capable of yielding prodigious expansion of NK cells (35,37). Given the experience with K562, which alone yields only modest results, genetic modification of KL-1 using vectors such as mb-IL-21 and 4-1BBL, will likely further enhance its capacity to activate and expand NK cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of irradiated B cells led to approximately 740-fold increase in NK cell number; these results are comparable with the genetically modified approaches described earlier. A recent report describes the use of K562 cells expressing membranebound IL-21 capable of yielding prodigious expansion of NK cells (35,37). Given the experience with K562, which alone yields only modest results, genetic modification of KL-1 using vectors such as mb-IL-21 and 4-1BBL, will likely further enhance its capacity to activate and expand NK cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly studied feeder line is the class Inegative leukemic line, K562, which, in unmodified form, yields modest NK cell expansion (33,34). Genetically modifying K562 to express 4-1BB ligand and MIC-A together with soluble IL-15 led to a 200-fold increase in cell number but obtained a final product containing only 56% NK cells (35). By engineering expression of membrane-bound IL-15 and 4-1BBL, a 150-fold expansion of NK cells was achieved after 15 days of culture with 90% purity (26).…”
Section: Discussionmentioning
confidence: 99%
“…Another study used K562 cells that had been transduced to express IL-15/IL-15R␣ to expand and activate human NK cells ex vivo for future adoptive transfer of these cells. 35 Adoptive transfers of NK cells have shown limited clinical benefit in terms of antitumor responses. Although NK cells have been shown to successfully engraft, expand, and migrate to tumor sites after adoptive transfer, 36 clinical trials showed mixed results ranging from no changes in patient survival or metastasis occurrence to slight improvements.…”
Section: Clinical Utilization Of Nk Cellsmentioning
confidence: 99%
“…Additionally, K562 feeder cells genetically modified to coexpress MICA, 4-1BB ligand and IL-15 (K562-MICA-4-1BBL-IL-15) showed potential for ex vivo NK cell expansion for clinical immunotherapy. 167 Compared with mbIL15, K562-based genetically engineered artificial antigen-presenting cells with membrane-bound IL-21 supported human NK cell proliferation with longer telomeres and less senescence, resulting in enhanced expansion and tumor killing. 168 Large-scale in vitro-expanded NK cells using irradiated Epstein-Barr virustransformed lymphoblastoid cell lines feeder cells were also found to be more cytotoxic to tumor cells, with upregulated activating receptors and death receptor ligands as well as altered cytokine secretion profiles.…”
Section: Expanding Nk Cells For Clinical Practicementioning
confidence: 99%
“…As summarized in Table 2, Epstein-Barr virustransformed lymphoblastoid cell lines, genetically modified K562 cells, or irradiated autologous cells were used as feeder cells to promote NK cell expansion from PBMCs. [164][165][166][167] The Campana group has developed a master cell bank of K562 feeder cells expressing a membrane-bound form of IL-15 (mbIL15) and 4-1BB ligand (K562-mb15-41BBL) under cGMP guidelines, and demonstrated that large-scale expansion and activation of human NK cells for clinical studies was feasible. 165 These NK cells demonstrated cytotoxic activity toward tumor cells even higher than observed in the initial small-scale experiments.…”
Section: Expanding Nk Cells For Clinical Practicementioning
confidence: 99%